THE IMPLEMENTATION OF FLASHCARD GAME ON VOCABULARY MASTERY - Yunitaka Baharudin, Dinar Vincy (Universitas Islam Madura, 2015)
Learning vocabulary is difficult for some students. There are a number of factors causingÂ the difficulty of learning vocabulary: first is from studentsâ point of view who argued thatÂ a lot of various different vocabularies should be learned by the students in a short time inÂ which they memorize them but often forget. Second is from teacherâs point of view whoÂ said that teachersâ technique (traditional memorization) and media (power point) inÂ teaching vocabulary were almost never changed for a long time. Therefore this study isÂ aimed at investigating the effectiveness of teaching vocabulary using flashcard game onÂ vocabulary mastery.